Descriptive study of clinical profile of severe preeclampsia - Gusain, Nisha; Mule, Vidya Dinkar; Lalgudi, Swetha Sekar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: The study was conducted to find out the frequency, risk factors, maternal complications, fetal outcome, the early intervention and treatment in cases of severe preeclampsia in a tertiary care centre. Methods: It was a descriptive observational study conducted at department of obstetrics and gynecology for the duration of 18 months. Severe preeclampsia diagnosed by clinical features, risk factors identified by history taking, treatment given according to institutional protocol, maternal and neonatal outcome was analysed. Results: Frequency of severe preeclampsia was 1.3%. Majority of the patients belong to the age group of 20-30 years. Risk factors recorded- raised BMI, primiparity, previous preeclampsia history 56.7% patients underwent LSCS. Complications noted- eclampsia, abruption, PPH, renal failure and HELLP syndrome. 60.5% neonates were having low birth weight (<2.5 kg). Perinatal mortality was found in 14.9% of neonates. Most common reason for maternal ICU admission- ARF followed by DIC, eclampsia. There was no maternal mortality in our study. Conclusions: Adequate antenatal visits, good antenatal care and NICU care can reduce the morbidity and mortality. For early detection of cases, regular blood pressure monitoring by family physician is essential in predisposed individuals. Early reporting to the institute on development of symptoms, timed termination of pregnancy, wider use of magnesium sulfate, availability and implementation of emergency obstetric care reduces the morbidity and mortality. Although the number of patients undergoing LSCS is more, a fair amount of induction trial can be given with proper monitoring services.